Spousal Support and Resilience during the COVID-19 Pandemic: From the Perspectives of Cleaning Staffs Working on Hospitals - Rahmadian, Laksmi; Ediati, Annastasia (Faculty of Psychology, Universitas Diponegoro, 2022)
Health practitioners received great attention during the COVID-19 pandemic due to their pivotal role in treating the affected individuals. However, lack of attention was given to supporting workers in the hospital such as cleaning staffs. The study aims toinvestigate whether spousal support was associated with resilience on cleaning staffs working in hospitals during the COVID-19 pandemic.The study participants comprised 103 cleaning staffswho work in several hospitals in the Central Java province. In order to collect the data, we used the Spousal Support Scale, the Resilience Scale, and socio demographic questionnaire that were delivered usingan online platform. Then we analyzed data using SPPS 25.0. This research used the Pearson correlation test and revealed a moderate positive correlation between spousal support and resilience (r = .411,p < .001). In addition, spousal support explains 16.9% of resilience. The majority of study participants received great support from their spouses and reported moderate resilience. Family support, particularly from the partner, play important role in supporting participants work during the pandemic. Future studies may investigate other factors associated with resilience on cleaning staffs or other supporting healthcare workers who work in the hospitalduring the COVID-19 pandemic.